Carvedilol Matrix Tablet: Formulation and In Vitro Assessment - Boidya, Joya; Hasan, Ikramul; Reza, Md Selim (Bangladesh Pharmaceutical Journal, 2020)
The present study was conducted for preparing and assessing different in-vitro characteristics of hydrophilic polymer based matrix tablets of carvedilol. Nine formulations of matrix tablet were prepared using three hydrophilic polymers having 1% of three different dissolution enhancers. The matrix formers were sodium-carboxy methyl cellulose, Methocel K4M CR, Methocel K100M CR and the dissolution enhancers were PEG 6000, Poloxamer 188 and Kollidon-CLSF. Formulations F-10, F- 13 and F-16 contained PEG 6000 as dissolution enhancer, formulations F-11, F-14 and F-17 contained Poloxamer 188 and formulations F-12, F-15 and F-18 contained Kollidon-CLSF. Tablet granules were evaluated for bulk density (0.293 ± 0.012 to 0.310 ± 0.004 g/ml), tapped bulk density (0.368 ± 0.013 to 0.380 ± 0.012 g/ml) and compressibility index (16.612 ± 1.868 to 22.834 ± 5.426). The data indicated satisfactory flow properties of granules during compression. The tablets were subjected to thickness (1.79±0.04mm), hardness (11.46 ± 1.06 kg/cm), and friability (0.26 ± 0.06%) measurements. The in vitro dissolution study was carried out for 12 hrs using USP type II dissolution apparatus in 6.8 buffer as the dissolution medium where release mechanisms were subjected to zero order, first order, Korsmeyer-Peppas, Hixson-Crowell and Higuchi kinetic studies. The order of dissolution enhancing power was PEG 6000 > Poloxamer 188 >Kllidon-CLSF. The drug release from the tablets followed erosion mechanisms. Among all the formulation F-13, F-14 and F-17 exhibited USP complied in vitro dissolution profiles. Bangladesh Pharmaceutical Journal 23(1): 26-31, 2020